БАДИИЙ МАТНДА ФРАЗЕОЛОГИК ПОЛИСЕМИЯНИНГ ЛИСОНИЙ ТАДҚИҚИГА ДОИР - Рахимова, С.Ж. (SCIENCE and SOCIETY, 2020)
The article is based on a linguistic and stylistic analysis of phraseological polysemy in a literary text with specific conclusions. The study of the subject was classified and reacted to a certain extent. Based on the examples from the interpretation, some propositions were described that differentiate the meanings of phraseological units in the context, as well as the multiplicity and polysemy of expressions.